Impact of one‐time testing for Trypanosoma cruzi antibodies among blood donors in the United States. Issue 3 (26th December 2018) - Dodd, Roger Y.; Groves, Jamel A.; Townsend, Rebecca L.; Notari, Edward P.; Foster, Gregory A.; Custer, Brian; Busch, Michael P.; Stramer, Susan L.
Abstract : BACKGROUND: US blood donors are tested for Trypanosoma cru z i antibodies only at their first presentation, based on studies, reviewed here, demonstrating the absence of incident infections. Reports of autochthonous human transmissions of the parasite in Texas have raised concern about the safety of one‐time testing. METHODS: Positive donation frequencies were evaluated among first‐time blood donations from 2007 to 2015. Rates and their temporal changes were evaluated in an area of high T. cruzi infection and compared with rates elsewhere. Donors with positive results were surveyed for risk factors and relevant demographic characteristics. RESULTS: Data from 9.1 million first‐time donations were analyzed; 585 (1:15, 544) were confirmed positive by radioimmunoprecipitation assay (RIPA) or concordantly positive with a second screening test/licensed assay. Seroprevalence in first‐time donors in Southern California (an area of high endemicity) was 1:2, 747, or 5.7‐fold higher than the overall rate. Rates did not change over time nationally but showed a nonsignificant consistent downward trend in Southern California. The majority (92%) of donors who responded to a questionnaire had one or more T. cruzi endemic‐area risk factors. Five donors with likely autochthonous infection were identified (2007–2013); nine additional donors had RIPA false positivity. CONCLUSION: T. cruzi seroprevalence among donors nationally and in an area of high enzootic infection were stable or declining. Almost all interviewed seropositive donors had known risk factors indicating likely infection years earlier while residing in T. cruzi –endemic areas. In the United States, there was no evidence of increased T. cruzi prevalence among first‐time donors.